2015
DOI: 10.14260/jemds/2015/1025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 57 Post - Endophthalmitis R Etinal D Etachment and Predi Ctive Factors for Visual Outcome

Abstract: OBJECTIVE: Evaluation of cases of endophthalmitis developing Rhegmatogenous retinal detachment and managed with vitreoretinal surgery, their clinical profile, factors responsible for retinal detachment and the predictive factors for the final outcome. SETTING: Vivekanand Netralaya, Lions NAB Eye hospital, Miraj. MATERIAL AND METHODS: This is a retrospective nonrandomized case series involving 57 consecutive cases of post endophthalmitis Rhegmatogenous Retinal Detachment. 168 cases of endophthalmitis that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Nelsen et al 9 reported that postoperative causes of endophthalmitis were most frequently complicated by RD. Som et al, and Dave et al however, found that posttraumatic causes were the most frequent, 7,10 and Lee et al, 11 contrarily, found that endogenous etiology was associated with a higher rate of RD. Finally, in the EVS, management of the endophthalmitis by pars plana vitrectomy (PPV) or tap-and-inject did not change the rate of subsequent RD.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Nelsen et al 9 reported that postoperative causes of endophthalmitis were most frequently complicated by RD. Som et al, and Dave et al however, found that posttraumatic causes were the most frequent, 7,10 and Lee et al, 11 contrarily, found that endogenous etiology was associated with a higher rate of RD. Finally, in the EVS, management of the endophthalmitis by pars plana vitrectomy (PPV) or tap-and-inject did not change the rate of subsequent RD.…”
mentioning
confidence: 97%
“…2 In the current literature, the rate of RD post endophthalmitis varies from 7% to 34%. [3][4][5][6][7] There are inconsistent findings regarding whether certain causative organisms, etiologies, or management approaches for endophthalmitis are more likely to be complicated by RD. In the endophthalmitis vitrectomy study (EVS), endophthalmitis caused by more virulent organisms, specifically gram-negative bacteria and gram-positive organisms that were not coagulasenegative micrococci, was more likely to be complicated by RD.…”
mentioning
confidence: 99%